Karakteristik Balok Laminasi Dari Batang Kelapa (Cocos Nucifera L.) Dan Kayu Kemiri (Aleurites Moluccana Wild.) (Characteristics of Glued Laminated Beams of Coconut Trunk (Cocos nucifera L.) and Candlenut Wood (Aleurites moluccana Wild.) - Iwan Risnasari; Irawati Azhar; Astri Novita Sitompul (FORESTA, 2012)
The Utilizing forest as source of wood raw materials is tend to increase, while the supply of wood is limited. As a result it can influenced the sustainable of ecosystem and the forest condition it self. The main objective of this was to find out the substitution of construction board (lumber and plywood). This research concerned to using coconut trunk and kemiri wood as alternative raw material in producing glued laminated beams. It is needed by industrial sector as a raw material because wood has been limited and it may solve environmental problem. In this research, the treatment is number of layer on glued laminated beam (3 layer, 5 layer, and 7 layer). Coconut trunks were used as outer layers and kemiri wood was used as midle layer and bonded by Isocyanate and PVAc by different ratio of 100:15. Evaluation on physical and mechanical properties were measured based on ASTM D 198-05. The results showed: 1). The value of density of gluelam were in the range 0,63–0,68 g/cm3 2). The value of moisture content were in the range 14,14-14,37 % 3). The value of water absorption for 2 and 24 hours were in the range 8,61- 8,74 % and 21,09-21,29 % 4). The value of thickness swelling for 2 and 24 hours were in the range 0,79-0,80 % and 1,57-,59 % 5). Modulus of elasticity (MOE) value were in the range 7519,63-18358,40 kgf/cm2 6). Modulus of rupture (MOR) value were in the range 180,34-364,04 kgf/cm2 7). Internal bond (IB)value were in the range 2,48-3,95 kgf. Layers of glued laminated beams are not significantly influence the value of physical and mechanical properties, except the value of MOR. The best result achieved in this research is the beam prepared from 3 layers.Keywords : Coconut trunk, kemiri wood, glued laminated beams, physical and mechanical properties.